Implication of the Annexin 1/FPR axis in leishmanial exosome-mediated Leishmania major skin hyperpathogenesis - da Silva Lira Filho, Alonso; Lafleur, Andrea; Alvarez, Fernando; Piccirillo, Ciriaco A.; Olivier, Martin (Frontiers in Immunology, 2024)
Introduction: Exosomes produced by the protozoan parasite Leishmania (LeishEXO) are wellestablished drivers of virulence, though mechanisms underlying their exacerbation of experimental leishmaniasis remain elusive. Expression of Annexin A1 (ANXA1), a protein implicated in exosomemediated pathologies and viral internalization, has been shown to correlate with cutaneous leishmaniasis severity. Given ANXA1's regulation of myeloid cellsthe canonical hosts for Leishmaniawe studied the potential role of ANXA1 and its receptors FPR1/2 in exerting LeishEXO's effects. Methods: Murine and in vitro ANXA1 -/-models were used to study the generation of protective TH1 responses during experimental L. major infection with and without LeishEXO. Recruitment of inflammatory cells was assessed using a peritoneal cell recruitment assay and immunophenotyping, and production of inflammatory mediators was measured using a cytokine and chemokine array. Treatment of experimental models with FPR2 antagonist WRW4 and FPR1/2 agonist WKYMVm was used to delineate the role of the FPR/ANXA1 axis in LeishEXO-mediated hyperpathogenesis. Results: We established that ANXA1 deficiency prohibits LeishEXO-mediated pathogenesis and myeloid cell infection, with minimal alterations to adaptive and innate immune phenotypes. FPR2 blockade with WRW4 similarly inhibited leishmanial hyperpathogenesis, while direct activation of FPRs with WKYMVm enhanced infection and recapitulated the LeishEXO-mediated phenotype. This research describes LeishEXO's utilization of the ANXA1/FPR axis to facilitate parasitic internalization and pathogenesis, which may be leveraged in the development of therapeutics for leishmaniasis.